Comparative proteomics of ovaries elucidated the potential targets related to ovine prolificacy - Li, Chunyan; Zhou, Mei; He, Xiaoyun; Di, Ran; Zhang, Zijun; Ren, Chunhuan; Liu, Qiuyue; Chu, Mingxing (Frontiers in Veterinary Science, 2023)
Small Tail Han (STH) sheep, a unique Chinese breed, is recognized for its early maturity, year-round estrus, and prolificacy. However, the molecular mechanism of its high prolificacy has not been fully elucidated. The Proteomics approach is feasible and effective to reveal the proteins involved in the complex physiological processes of any organism. Given this, we performed the protein expression profiling of ovarian tissues during the luteal phase using polytocous STH sheep (litter size ≥2, three consecutive lambings) and monotocous STH sheep (litter size =1, three consecutive lambings) (PL vs. ML), and the follicular phase using polytocous STH sheep (litter size ≥2, three consecutive lambings) and monotocous STH sheep (litter size =1, three consecutive lambings) (PF vs. MF), respectively. Parallel Reaction Monitoring (PRM) was conducted to validate the differentially abundant proteins (DAPs). The tandem mass tag (TMT) quantitative proteomic results showed that a total of 5,237 proteins were identified, of which 49 and 44 showed differential abundance in the PL vs. ML and PF vs. MF groups, respectively. Enrichments analyses indicated that the DAPs including TIA1 cytotoxic granule-associated RNA-binding protein-like 1 (TIAL1), nicotinamide phosphoribosyltransferase (NAMPT), and cellular retinoic acid-binding protein 1 (CRABP1) were enriched at the luteal phase, while TIAL1, inhibin beta-a-subunit (A2ICA4), and W5PG55 were enriched at the follicular phase, potentially mediating reproductive processes in polytocous ewes. Furthermore, six DAPs were verified using PRM, confirming the accuracy of the TMT data acquired in this study. Together, our work expanded the database of indigenous sheep breeds and provided new ovarian candidate molecular targets, which will help in the study of the genetic mechanisms of ovine prolificacy.